The effect of motivation and job training on the performance of employees of the population and civil registration office of Tangerang Regency - Nadiya Ambarwati; Herayati Herayati; Martinus Wahyu Purnomo (Trigin Publisher, 2023)
Based on the research, the authors tried to identify the effect of motivation and job training on employee performance at the Department of Population and Civil Registration of Tangerang Regency. Aims to determine the effect of motivation and job training on employee performance. The method used is statistical quantitative using 38 respondents and data collection techniques in the form of questionnaires. The data obtained were analyzed using multiple linear regression analysis. The results showed that the level of significance for the effect of motivation on employee performance was 4.655. However, the significance value is > 0.05, which means that motivation has no significant effect on employee performance. Therefore, the first hypothesis which states that motivation affects employee performance at the Department of Population and Civil Registration of Tangerang Regency is rejected. However, the results of the study also show that job training has a significant effect on employee performance. The significance level for the effect of job training on employee performance is 13.588. The results of the F test analysis show that the variables of motivation and job training have a significance value of 0.000, which is <0.05. In addition, the calculated f value (809.807) is also > from f table (3.267). So, it can be concluded that the variables of motivation and job training have a significant influence on employee performance.